Anti-Inflammatory Activity Test fo Ethanol Extract of Kluwih Leaves (Artocarpus camansi Blanco) on Male Wistar White Rats (Rattus norvegicus) - Nofiyanti, Laela Suci; Sunarti; Samodra, Galih (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Inflammation occurs when the body reacts to infection, irritation, or other damage. Some compounds in kluwih leaves are believed to have anti-inflammatory potential, one of which is flavonoids. The aim of this study was to find out the activity and effective dosage of the ethanol extract from kluwih leaves as an anti-inflammatory in male white Wistar rats. The experimental animals were divided into five groups: the negative control group (0.5% Na-CMC), the positive control group (Na-diclofenac), and the three treatment groups were given ethanol extract from kluwih leaves at doses of 175, 350, and 700 mg/KgBW orally. After 30 minutes, the soles of the rats' feet were induced with 0.1 ml of 1% carrageenan subplantarly. Edema volume was assessed every 1 hour for 6 hours using a plethysmometer. The data was statistically analyzed using One-Way ANOVA with LSD post hoc test. The research data shows that the ethanol extract of kluwih leaves at doses 175, 350, and 700 mg/KgBW has anti-inflammatory activity. The effective dose of kluwih leaf ethanol extract was 700 mg/KgBW (28.68%) with the second highest percentage of anti-inflammatory power value after the positive control group (31.75%). The LSD (Least Significant Difference) results indicate that the ethanol extract of kluwih leaf at a dose of 700 mg/KgBW does not show a significant difference in its anti-inflammatory effect with the positive control (0.442>0.05).